MYSTICISM IN DIFFERENT RELIGIOUS TRADITIONS - de Sousa, Pio (Journal of Dharma, 1988)
In various cultures and in various ages through myth and mystery mystics have struggled to put into words the strange insights they received. Thus have developed the great religions of the world. To the common man these insights were hardly intelligible. The paths traced by the mystics were too difficult, and so some disciples developed rituals to give some experience of the divine to common folk, whose credulity was unfortunately exploited by vested religion. However, many have always been experimenting for themselves (perhaps not so many in the Christian tradition because of its strong regimentation, except among monks and the religious). Their experiences and writings I have been very valuable guides to other seekers. Most of them pointed to the need for quiet silent introspection - in Indian terms antaradrishti, which is not the same as an introspection. Introspection is examining one’s thoughts, feelings and mental processes. Antaradrishti emphasizes looking inwards, not so much examining as seeing, experiencing and learning, being aware of one’s true interiority.